Integration of Croatian farmers in the EU information society – issues and implications (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2015)
Further development of family farms in Croatia largely depends on their adaptation to the contemporary demands of the open market, in particular by keeping up with new technologies and acquiring new knowledge. Through such adaptation, farmers would gain better access to information and new markets and a better position in negotiations. Overall, they would become better managers of their businesses. The Internet, coupled with other information and communication technologies (ICT), represents a tool for linking up different interest groups within the vertical agricultural chain. The role and significance of ICT and information literacy within agricultural activities is presented through a review of European development initiatives and theoretical insights regarding this topic. To reveal obstacles (objective and subjective), the current level of skills and the readiness to adopt new knowledge and technologies, a survey was conducted on a representative sample of inhabitants from rural areas, i.e. farmers, since they are a determining factor of such changes. The present paper is part of the research exploring a wider context of ICT implementation aimed at enhancing farmers’ competencies, and consequently, enhancing overall agricultural performance. The analysis seeks to confirm the basic hypothesis that there are objective and subjective obstacles, but also the interest and willingness to increase the level of knowledge in the observed social unit.Keywords: Information society, ICT, Croatian farmers, social marketing